Effect of experimental primers on hydrolytic stability of resin zirconia bonding. Issue 10 (19th May 2017) - Khan, Aftab Ahmed; Al Kheraif, Abdulaziz Abdullah; Syed, Jamaluddin; Divakar, Darshan Devang; Matinlinna, Jukka Pekka
Abstract: This study assessed the effect of experimental silane primers and two adhesive resin cements on resin zirconia adhesion strength. The surfaces of cut Y-TZP zirconia blocks (Lava™ Frame), 16 mm × 16 mm × 4.5 mm, were pretreated twice. First, they were grit-blasted with Korox™ alumina powder (110 μm) followed by silica-coating with Rocatec™ Soft. Next, the blocks were randomly assigned into eighteen sub-groups ( n  = 6, N  = 108) according to three primers (control ESPE Sil™, 1.0 vol.-% 3-acryloxypropyltrimethoxysilane, and 1.0 vol.-% 3-acryloxypropyltrimethoxysilane + 0.5 vol.-% bis -12-(triethoxysilyl)ethane), two in dentistry used resin cement products (Multilink™ Speed, and Multilink™ N), and three storage conditions (24 h dry, 1 month immersed in distilled water, and 6 months immersed in distilled water at room temperature) used. Onto each pretreated zirconia block, four cylindrical resin composite cement stubs were prepared and light-cured. The surface roughness, contact angle, and adhesion (shear bond) strength (SBS) were measured, and statistically analyzed (ANOVA, the Tukey's test, p  < 0.05). No statistical differences were observed in surface roughness values of different primer-treated zirconia groups. After six months of water aging, the shear bond strength of the groups that employed 1.0 vol.-% 3-acryloxypropyltrimethoxysilane (9.0 MPa ± 0.8 MPa), and the blend of 1 vol.-% 3-acryloxypropyltrimethoxysilane + 0.5 vol.-% bis -12-(triethoxysilyl)ethane (8.9 MPa ± 2.0 MPa) with Multilink™ Speed resin composite cement were statistically insignificantly higher compared to using ESPE Sil™ (8.7 MPa ± 1.8 MPa). The experimental primers may have potential to be used for long-term resin zirconia adhesion.